VD_FINDINFO Décision / 2023 / 218 vom 17. März 2023 - VD Tribunal cantonal (2023)
DÉFENSE OBLIGATOIRE, PREUVE ILLICITE, AUDITION OU INTERROGATOIRE | 130 CPP (CH), 130 let. b CPP (CH), 131 CPP (CH), 141 CPP (CH)